Geodynamics of paleo-Pacific plate subduction constrained by the source lithologies of Late Mesozoic basalts in southeastern China - Zeng, G.; He, Z.; Li, Zhen; Xu, X.; Chen, L. (American Geophysical Union, 2016)
Widespread Late Mesozoic volcanic magmatism in southeastern China is generally thought to represent products in response to the subduction of paleo-Pacific plate; however, it remains unclear when this process began to affect the mantle and the related magmatism. Here we present a systematic study on the source lithology of Late Mesozoic basalts in this area to highlight a link between lithological variations of mantle and subduction process of paleo-Pacific plate. Late Mesozoic basalts can be subdivided into four groups based on their erupted ages: 178~172 Ma, approximately 150 Ma, 137~123 Ma, and 109~64 Ma. The primary source lithology of these rocks is pyroxenite rather than peridotite, and this mafic lithology can be formed by either ancient or young recycled crustal components. Notably, the source lithology of the approximately 150 Ma and 137~123 Ma basalts is primarily SiO2-rich pyroxenite, and the former is carbonated. The discovery of carbonated, SiO2-rich pyroxenite reflects the influence of a recently recycling event in the mantle. The subduction of paleo-Pacific plate is the most appropriate candidate and can be responsible for the mantle-derived magmatism after approximately 150 Ma in southeastern China. Therefore, we suggest a paleo-Pacific slab rollback with increased dip angle as a possible model to control the lithological variations of Late Mesozoic mantle beneath southeastern China.